Studies for the Multimerization of DAB‐1‐Based Iminosugars through Iteration of the Nitrone Cycloaddition/Ring‐Opening/Allylation Sequence. Issue 30 (23rd July 2019) - Matassini, Camilla; D'Adamio, Giampiero; Vanni, Costanza; Goti, Andrea; Cardona, Francesca
Abstract : Multivalent iminosugars have gained the attention of the research community in the last ten years. We report herein the proof of principle for an original synthetic strategy to build multivalent iminosugars based on the natural DAB‐1 moiety as the bioactive epitope. The synthesis relies on the iteration of three selective and high‐yielding steps (1, 3‐dipolar cycloaddition to nitrone1, N‐O bond cleavage of the adduct and selective N ‐ and/or O ‐allylation), and allows the preparation of different topologies of the final DAB‐1 clusters. Abstract : Multimeric iminosugars with different topologies based on DAB‐1 were obtained through the iteration of a three step sequence involving 1, 3‐dipolar cycloaddition of nitrone1, N‐O bond cleavage, and N ‐, O ‐ or N, O ‐bis allylation.